2019
DOI: 10.1111/tbed.13319
|View full text |Cite
|
Sign up to set email alerts
|

Molecular xenomonitoring and host identification of Leishmania sand fly vectors in a Mediterranean periurban wildlife park

Abstract: The epidemiological cycle of zoonotic phlebotomine‐borne Leishmania infantum is a complex system in which domestic animals and wildlife interact and participate in its maintenance and transmission. In this study, we combined entomological surveillance, xenomonitoring of L. infantum and identification of host feeding sources of engorged females to investigate the potential contribution of a periurban wildlife park to leishmaniosis in neighbouring residential areas. Overall, 7,309 sand flies were collected in 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…Moreover, other mammal blood sources were identified in engorged S. minuta in our study, revealing a possible opportunistic feeding behaviour. This conduct has also been observed in Sergentomyia dentata from Turkey (Özbel et al, ) and in other sand fly species as P. perniciosus (González, Álvarez, et al, ; Muñoz et al, ; Tarallo, Dantas Torres, Lia, & Otranto, ). Despite the noticeable result about the S. minuta feeding behaviour, the rate of blood meal identification was under the expectations according to studies performed in sand flies from the same region (González, Jiménez, et al, ), but similar to the rates showed in studies carried out in Portugal (Maia et al, ).…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, other mammal blood sources were identified in engorged S. minuta in our study, revealing a possible opportunistic feeding behaviour. This conduct has also been observed in Sergentomyia dentata from Turkey (Özbel et al, ) and in other sand fly species as P. perniciosus (González, Álvarez, et al, ; Muñoz et al, ; Tarallo, Dantas Torres, Lia, & Otranto, ). Despite the noticeable result about the S. minuta feeding behaviour, the rate of blood meal identification was under the expectations according to studies performed in sand flies from the same region (González, Jiménez, et al, ), but similar to the rates showed in studies carried out in Portugal (Maia et al, ).…”
Section: Discussionsupporting
confidence: 68%
“…Zoos and wildlife parks with non-autochthonous and stabled fauna are excellent sites for studying the ecology and epidemiology of vector-borne pathogens, as studies of sand flies (9,10), biting midges Culicoides (11), and mosquitoes (12)(13)(14)(15) have previously shown. Given that captive animals are housed in known locations, the flight distances of captured insect vectors containing blood from these animals can be accurately estimated (10).…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted in a 16‐ha wildlife park situated on the outskirts of the city of Murcia in southeast Spain (Fig. ) (Muñoz et al ., ), where L. infantum is endemic (Perez‐Cutillas et al ., 2015; Goyena et al ., 2016; Risueño et al ., 2018). The park was home to 200 wild mammals of 30 species, 15 reptiles of three species and 300 birds of 26 species, kept in large, earth‐floored, open enclosures (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, the costs borne by the insect in reaching an accessible host and subsequently finding a suitable breeding site were not considered. The present study used data on Phlebotomus vector abundances and feeding host diversity from a previous study (Muñoz et al ., ) to investigate sandfly vector feeding preferences, assuming that the majority of sandflies displayed site fidelity. The study estimated the probability that an engorged female collected in a light trap would feed from a particular host species when other species were available nearby, taking into account travelling costs, host census and environmental trapping site differences.…”
Section: Introductionmentioning
confidence: 99%